Synthesis, Bonding, and Reactivity of Vanadium(IV) Oxido-Fluorido Compounds with Neutral Chelate Ligands of the General Formula cis-[VIV(=O)(F)(LN-N)2]+ - Passadis, Stamatis S.; Tsiafoulis, Constantinos G.; Drouza, Chryssoula; Tsipis, Athanassios C.; Miras, Haralampos N.; Keramidas, Anastasios D.; Kabanos, Themistoklis A. (My University, 2016)
Reaction of the oxidovanadium(IV)-LN-N species (LN-N is bipy = 2,2′-bipyridine or bipy-like molecules) with either BF4- or HF and/or KF results in the formation of compounds of the general formula cis-[VIV(=O)(F)(LN-N)2]+. Structural and spectroscopic (electron paramagnetic resonance) characterization shows that these compounds are in the tetravalent oxidation state containing a terminal fluorido ligand. Density functional theory calculations reveal that the VIV-F bond is mainly electrostatic, which is reinforced by reactivity studies that demonstrate the nucleophilicity of the fluoride ligand in a halogen exchange reaction and in fluorination of various organic substrates.
Keywords: Oxidation; Oxidovanadium; General formula